Effects of hyperhomocysteinemia and betaine-homocysteine S-methyltransferase inhibition on hepatocyte metabolites and the proteome - Selicharová, Irena; Kořínek, Marek; Demianová, Zuzana; Chrudinová, Martina; Mládková, Jana; Jiráček, Jiří (Biochimica et biophysica acta, 2013)
Both cardiovascular disease and liver injury are major public health issues. Hyperhomocysteinemia has been linked to cardiovascular diseases, and defects in methyl group metabolism, often resulting in hyperhomocysteinemia, are among the key molecular events postulated to play a role in liver injury. We employed proteomics and metabolomics analyses of human hepatocytes in primary cell culture to explore the spectrum of proteins and associated metabolites affected by the disruption of methyl group metabolism. We treated the hepatocytes with homocysteine (Hcy, 0.1mM and 2mM) to follow the impact of hyperhomocysteinemia, and in parallel, we used a specific inhibitor of betaine-homocysteine S-methyltransferase (BHMT) to extend our understanding of the physiological functions of the enzyme. The major effect of BHMT inhibition was a 50% decrease in S-adenosylmethionine levels. The treatments with Hcy resulted in multiple changes in the metabolite levels depending on the treatment modality. The BHMT inhibition and 0.1mM Hcy treatment induced only moderate changes in the hepatocyte proteome and secretome, while the changes induced by the 2mM Hcy treatment were extensive. Phosphatidylethanolamine carboxykinase and ornithine aminotransferase were up-regulated about two fold indicating an intervention into metabolism. Cellular proliferation was suspended, secretome composition was changed and signs of apoptosis were discernible. We have detected fibrinogen gamma dimers, which might have a role as a potentially new biomarker of early liver injury. Finally, we have demonstrated the failed maturation of apolipoprotein A1, which might be a new mechanism of disruption of cholesterol efflux from tissues.
Keywords: hepatocyty; fibrinogen; 2D gelová elektroforéza; proliferace buněk; apoptóza; kolorektální nádory; apolipoprotein A-I; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Blotting, Western; proteom; betain-homocystein-S-methyltransferasa; Apolipoprotein A-I; Apoptosis; hyperhomocysteinemie; Colorectal Neoplasms; Proteome; Betaine-Homocysteine S-Methyltransferase; lidé; nádory jater; S-Adenosylmethionine; Metabolomics; Hyperhomocysteinemia; kultivované buňky; Hepatocytes; Protein Multimerization; homocystein; western blotting; metabolomika; S-adenosylmethionin; Cells, Cultured; Liver Neoplasms; Male; Electrophoresis, Gel, Two-Dimensional; Cell Proliferation; Homocysteine; lidé středního věku; Fibrinogen; multimerizace proteinu; spektrometrie hmotnostní - ionizace laserem za účasti matrice; mužské pohlaví; Middle Aged; Humans